Improvement in pulmonary function in asthmatic patients after bariatric surgery: a systematic review and meta-analysis - Upala, Sikarin; Thavaraputta, Subhanudh; Sanguankeo, Anawin (Surgery for obesity and related diseases, 2019)
•The effect of bariatric surgery on pulmonary function in asthmatic patients is inconclusive. This systematic review and meta-analysis investigated the effect of bariatric surgery on pulmonary function (forced expiratory volume in one second (FEV1), forced vital capacity (FVC), and FEV1/FVC) in patients with asthma.•A statistically significant increase in FEV1 and FVC was observed after bariatric surgery.•No significant post-surgical improvement was observed for FEV1/FVC. The association between obesity and asthma is well-established. Some evidence suggests that weight loss may improve asthma outcomes; however, the effect of bariatric surgery on pulmonary function in asthmatic patients remains inconclusive. This systematic review and meta-analysis of observational studies assessed the impact of bariatric surgery on patients with asthma. To investigate the effect of bariatric surgery on pulmonary function in patients with asthma. Systematic review and meta-analysis of published studies. A comprehensive search of the MEDLINE, EMBASE, and Cochrane Central Register of Controlled Trials (CENTRAL) databases was conducted. The sole inclusion criterion was published studies that evaluated the effects of bariatric surgery on pulmonary function in asthmatic patients. The outcomes of interest were forced expiratory volume in 1 second (FEV1), forced vital capacity (FVC), and FEV1/FVC. A meta-analysis of studies comparing pre- and postsurgery spirometric measures, and of studies comparing surgery and control groups was performed. From 25 full-text articles, 6 observational studies met the inclusion criteria and were included in this meta-analysis based on the random-effects model. A significant increase in FEV1 and FVC was observed after bariatric surgery among studies without a control group (mean difference: .21 L, 95% confidence interval: .07–.35 for FEV1, and mean difference: .34 L, 95% confidence interval: .14–.53 for FVC). There was no significant change in FEV1/FVC after bariatric surgery compared with control. FEV1 and FVC were both found to be significantly improved after bariatric surgery; however, no significant postsurgical improvement was observed for FEV1/FVC.